The online learning benefits for the speaking skill improvement in A2 level class N3Q learners in the language center at Universidad Estatal de Bolívar. - Caicedo Quiñonez, Tania Eleana (2023)
The current research project entitled "The online learning benefits for the speaking skill improvement in A2 level class N3Q learners in the Language Center at Universidad Estatal de Bolívar" aims to analyze the online learning benefits of improving A2 learners' speaking skills. It is qualitative research, and it frames to the descriptive level. Besides, the study carries out an ethnographic and Bibliographical Documental modality. The technique used for the investigation was observation; consequently, the instrument was an observation guide to collect relevant and reliable data. The population comprises 25 A2 level class N3Q learners at the Language Center from Universidad Estatal de Bolívar. Based on the results, the researcher could identify that online learning provides benefits for improving EFL learners' speaking skills. Interaction between classmates and teachers is one of the most noticeable benefits because online learning allows teachers and learners to interact by using different digital tools. Therefore, Vocaroo and Voki are the most valuable digital tools to encourage learners to train their speaking skills. However, it is essential to consider that teachers must be careful about digital tools and activities used in the classroom because they play an indispensable role when teaching speaking skills.